PENGARUH PEMBERIAN KONTRAS MEDIA NON IONIK LOW OSMOLAR INTRA VENA TERHADAP KADAR CYSTATIN–C SERUM PADA ORYCTALAGUS CUNICULUS - Bintoro, Ariyo Sakso; Soetojo, Soetojo; Soebadi, Doddy M (Indonesian Urological Association, 2008)
Objective: To measure effects of low osmolar non ionic contrast media on cystatin–C serum levels on different days after administration. Material and Method: Twenty-two oryctalagus cuniculus were divided into two groups of 11 subjects, each subject receiving intravenous injection of low osmolar non ionic contrast or a placebo solution (NaCl 0,9%). Cystatin-C serum levels of each subject were measured before injection, on days 1, 3, 7, and 10. Cystatin–C serum levels were determined with a sandwich ELISA method. Statistical analysis was performed with t–test. Results: Mean cystatin–C serum levels before injection was 0,00337 ± 0,00101 mg/L. Means from days 1, 3, 7, and 10 after injections were 0,00498 ± 0,00153 mg/L; 0,00565 ± 0,00247 mg/L; 0,00468 ± 0,00157, and 0,00339 ± 0,00188 mg/L respectively. Conclusion: Increase in serum cystatin–C levels on days 1, 3, and 7 was significant. On the 10th day no significant escalation was observed. Compared to the control group, there were significant differences in serum cystatin–C increase on days 1 and 3 in the intervention group, but no significant differences 7 and 10 days after injection.